Penerapan Model Problem Based Learning Untuk Meningkatkan Literasi Lingkungan Siswa SMA Negeri 2 Halmahera Barat - Anwar, Adrian Hi.; Amin, Astuti Muh.; Muna, Lintal (IAIN Ternate, 2023)
Problem Based Learning model teached students to increase environmental literacy and formulate solutions to environmental problems. Environmental literacy is a conscious attitude to pay attention and maintain the environment so that it was always maintained, sustainable, and maintained in balance. The conscious attitude in question was a sensitive attitude towards the environment and knowing the problems that occured. Someone who has knowledge about the environment, is not only limited to theory, but also able to be responsive and agile in overcoming various problems that occur in the surrounding environment. This study aims to analyze the effect of Problem Based Learning on environmental literacy in class X students of SMA Negeri 2 West Halmahera and to analyze the increase in environmental literacy of class X students of SMA Negeri 2 West Halmahera with the application of Problem Based Learning. This type of research is quantitative research using quasi-experiments (Quasi Experiments). The research was conducted at SMA Negeri 2 West Halmahera, Gam Ici street, Central Ibu district. The population used in this study were students of SMA Negeri 2 West Halmahera, with samples from class X C and class X D. The data and data sources in this study were pretest and posttest questions, teacher and student observation sheets, and environmental care attitude questionnaires. Data collection techniques in research using observation and tests. The data collected, then analyzed by prerequisite test (normality and homogeneity test), hypothesis test and N-Gain test.Keywords: Development of LKS, Tridacna, Widi Island